2005
DOI: 10.1016/j.joca.2005.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin polysulphates repress IL-1 and promote the accumulation of chondrocyte extracellular matrix

Abstract: CDPS is a novel polysulfated polysaccharide showing cartilage structure modifying effects in vitro as it improves the synthesis of aggrecan and the accumulation of CAM macromolecules. This effect probably resulted in part from the downregulation of IL-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This cytokines also blunt chondrocyte compensatory synthesis pathways required to restore the integrity of the degraded ECM [5,6,7] . Thus cytokines activate the enzymatic degradation of cartilage matrix and are not counterbalanced by adequate synthesis of inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…This cytokines also blunt chondrocyte compensatory synthesis pathways required to restore the integrity of the degraded ECM [5,6,7] . Thus cytokines activate the enzymatic degradation of cartilage matrix and are not counterbalanced by adequate synthesis of inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , all three α-, β- and γ-CDPS equally and significantly improved the synthesis and accumulation by chondrocytes of CAM macromolecules e.g. aggrecan, Type II collagen and fibronectin [17]. It was shown that this enhanced repair function resulted from a down-modulation of the autocrine catabolic IL-1 pathway: β-CDPS inhibited the synthesis of IL-6 in both normal and OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this enhanced repair function resulted from a down-modulation of the autocrine catabolic IL-1 pathway: β-CDPS inhibited the synthesis of IL-6 in both normal and OA chondrocytes. Although the experiments were not performed in the presence of IL-1-blocking antibodies, it is supposed that β-cyclodextrin affected the IL-1 loop and did not directly impede the production of IL-6 [17]. While in osteoarthritic chondrocytes both autocrine anabolic (IGF-1) and catabolic (IL-1) pathways are up-regulated, the selective inhibition of IL-1 resulted in a dramatic improvement of the repair function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations